PENGARUH MOTIVASI, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL THE GROVE SUITES BY GRAND ASTON JAKARTA - Efendi; Asmanandar (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the motivation, communication and work environment on employee performance at Hotel The Grove Suites by Grand Aston Jakarta. Design/methology/approach- The population in this study were all employees of Hotel The Grove Suites by Grand Aston Jakarta. With the sample used in this study as many as 148 people, by saturated sampling technique. Data analysis methods used in this study are validity test, reliability test, and classic assumption test. While the hypothesis testing includes F test, t test and partial correlation analysis and coefficient of determination (R2). Findings- The results of the analysis can be seen that motivation () communication () and work environment () have the significant influence on the performance of employees both partially and simultaneously. The correlation analysis (r) and the coefficient of determination () obtained the results of motivation have a significant effect on employee performance with a weak category of 4.08%. Communication has a significant effect on employee performance with a weak category of 4.24%, work environment influences the significance of employee performance with a weak category of 5.10%. While all variables have affect the performance of employees in the medium category by 31%, simulteneously.